INTERNATIONAL LEGAL MECHANISMS OF COOPERATION IN ANTI-MONEY LAUNDERING: CONTEMPORARY CHALLENGES AND PROSPECTS - Голота, Наталія (SWorldJournal, 2025)
The globalization of financial markets and digital transformation have fundamentally changed transnational financial crimes, challenging traditional AML/CFT cooperation mechanisms. Modern money laundering schemes use complex multi-jurisdictional structure